Factors Impacting Successfully Competing for Research Funding: An Analysis of Applications Submitted to the Plastic Surgery Foundation. Issue 2 (February 2015) - Hume, Keith M.; Giladi, Aviram M.; Chung, Kevin C.
Abstract : Background: Federal research funding is decreasing, forcing specialty organizations to have an increasingly important position in developing and fostering research. As the research and innovation arm of the American Society of Plastic Surgeons, The Plastic Surgery Foundation has a key role in supporting promising plastic surgery research. Understanding the grant review process and factors that contribute to funding well-written grant funding applications is essential for aspiring academic surgeons. Methods: All research grant applications submitted to The Plastic Surgery Foundation in 2012 and 2013 were evaluated. Each reviewer comment was assessed independently by two study team members and classified into key weakness categories. The chi-square test was used to compare results between funded and unfunded grants. Linear regression identified which critique elements corresponded to changes in scores, and logistic regression identified elements that predicted funding. Results: The authors analyzed 1764 comments from 240 applications. Of these, 55 received funding. Funded grants had significantly fewer reviewer comments in four of five weakness categories. As expected, funded grants received better (lower) scores. Concerns in the categories of plan for execution and other elements/grantsmanship significantly affected score and odds of funding. Conclusions: Ensuring that a grant addresses all required elements is important for receiving a low reviewer score. Our study demonstrates that plan for execution and grantsmanship influence reviewer scoring more than others. Investigators must clearly address items associated with conducting their experiments and performing the analysis. Investigators must also give equal attention to elements of overall quality and completeness to optimize chances of funding.